(untitled) (Journal of Laboratory Animal Science, 2025)
Monosodium glutamate (MSG) is widely used as a food additive worldwide and the safety of MSG has always been a matter of concern. This study was conducted to assess the effect of MSG on foetal development using zebrafish embryos. Zebrafish embryos were collected from the spawning group of a male: female ratio of 1:2. Fertilized embryos in the blastula stage were transferred into 24-well plates and kept at 26.5 ±1°C. MSG in the concentration of 300 mg/L, which was then serially two-fold diluted to 150 mg/L, 75 mg/L, 37.5 mg/L, 18.75 mg/L, 9.38 mg/L, 4.687 mg/L, 2.34 mg/L, was used for treatment, and the control wells contained 2mL of RO water. Observations were recorded 24, 48, 72, and 96 h post-fertilization. MSG induced toxicity, mainly delayed development, reduced melanin pigmentation, and pericardial edema in zebrafish embryos at concentrations of 100 mg/L and above. MSG caused a retarded growth from 24 h to 72 h, but growth by 96 h could recover the developmental delay. Hatching was delayed in the treatment group, and by 96h, all surviving embryos had hatched. Overall, it can be concluded that these developmental defects may be due to oxidative stress and neurotoxic effects of glutamate at concentrations above 100 mg/L. Thus, MSG is toxic to developing embryos and can delay growth and metabolism in a concentration-dependent manner.